Penerapan K3 Menggunakan HIRARC (Hazard Identification Risk Assessment and Risk Control) pada Perusahaan Konstruksi di Cilegon - Setiawan, Lucky; Rahmatullah, Asep; Muhammad, Irfan; Rini, Asih Setyo; Hanan, Siti; Pratama, Theo Raka Haris (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
One of the companies in the Cilegon area engaged in the construction industry has a high level of work risk. This company is required to implement an Occupational Safety and Health program to prevent workplace accidents.". Risk identification and assessment in this company has not used the HIRARC method as a basis for mitigation. This aims to identify the risk of work accidents, assess the risks, and recommend control measures. Based on the results of the data processing that has been carried out, the results show a low-risk risk value with a percentage of 0%, a moderate risk value with a percentage of 36%, a high-risk value with a percentage of 64%, and an extreme risk value with a percentage of 0%. Keywords: Construction, Hazard, HIRARC, Risk Control, Work Accident